(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2020)
The identification of the occurrence of 232Th, by measuring the energies of the children radioisotopes 228Ac, 208Tl, 212 Bi and 212Pb, in their places of origin, using the Mobile Lab for Identification of Radiological and Nuclear Agents - LabMovelRN, by discriminating their environmental concentration normal and NORM [1] is important for the performance of the operational teams of the Brazilian Army Chemical, Biological, Radiological and Nuclear Defense Institute (IDQBRN), optimizing their time of action, and reducing the chain of custody of the sample. Due to the operational difficulty of using HPGe detectors in LabMovelRN, an adaptation is being carried out in the laboratory in order to allow the analysis of 232Th in soil samples by the gamma spectrometry technique using scintillation detectors [2] of NaI (Tl) type well as the characterization of the response of this scintillator detector in energy, resolution and energy efficiency up to 3,000 keV.